Effect of high purity rice husk silica synthesised using solvent thermal treatment method on the properties of natural rubber compounds / Zainathul Akhmar Salim Abdul Salim - Zainathul Akhmar , Salim Abdul Salim (2021)
In recent years, research on bio-based materials, such as rice husk is steadily gaining momentum. Despite their huge developmental potential, rice husks are often left unutilised following the harvesting season, wasting a natural wealth that could be explored. Their high silica content makes them potential fillers to replace commercial precipitated silica (PS) in the rubber industry. For first series, highly pure silica with small particle size and high surface area was extracted from rice husks via solvent-thermal treatment, followed by leaching with different concentrations of hydrochloric acid (HCl). This treatment method was modified from TAPPI T204 (2007) and TAPPI T264 (1997) standards, which are used for wood extraction in the pulp and papermaking industry. For second series, characterisation on treated rice husk silica (RHS) was conducted. RHS that was leached with 1.0 M HCl recorded the highest particle purity with 99.99% of SiO2 content and the highest BET surface area of 234.25 m2/g compared with RHS leached with 0.01 M, 0.1 M, 2.0 M, and 3.0 M HCl. All RHS samples were in the amorphous state following incineration at 700°C for 4 hours. For third series, RHS sample with the highest purity was incorporated in NR compounds at 2, 4, 6, 8, and 10 parts per hundred rubber (phr). Even without surface modification, the RHS-filled NR compounds showed improvements in strength-related properties at the optimum loading of 4 phr. The thermal stability of the NR compounds had also improved with RHS addition. The properties of the RHS-filled NR compounds were further enhanced following RHS surface modification with silane coupling agents. Surface modification is vital to improve the compatibility between the hydrophilic RHS and the hydrophobic NR by making RHS hydrophobic, which reduced the filler-filler interaction. This transformation had also increased the cure rate of the rubber compounds because the silane-modified RHS stopped reacting with cure activators and accelerators, consequently increasing the cure efficiency. In fourth series, three types of silane coupling agents with different functional groups, which are namely; bis[3-(triethoxysilyl)propyl]tetrasulfide (TESPT), (3-mercaptopropyl)trimethoxysilane (MPS), and (3-aminopropyl)triethoxysilane (APTES) were used to modify RHS surface. The modified RHS samples were incorporated in NR at the optimum loading of 4 phr. The increased reinforcing efficiency due to the strong rubber-filler interaction greatly improved the mechanical, thermal, and dynamic mechanical properties of all silane-modified RHS-filled NR compounds. However, TESPT led to the most outstanding performance of the RHS-filled NR compound compared with the other two alkoxy-based silanes, in terms of cure characteristics, overall strength-related properties and thermal stabilities. In fifth series, the effectiveness of RHS as a filler was compared to PS. Both types of silica were modified with TESPT and incorporated in NR at 4 phr loading. The performance of RHS as a filler was equivalent to PS in most properties. This shows that RHS synthesised using the solvent-thermal treatment method is suitable to be used as NR filler.